2020
DOI: 10.29328/journal.ijcv.1001022
|View full text |Cite
|
Sign up to set email alerts
|

Serological and virological profile of patients with chronic hepatitis B infection in Eritrea

Abstract: Background Hepatitis B virus (HBV) infection is a major global public health threat especially in developing countries. The World Health Organization (WHO) estimates that in 2015, about 60 million Africans were living with chronic HBV infection [1]. Most African countries fall within the high endemicity regions [2]. Infection with HBV is usually acquired through perinatal or childhood exposure to the virus, contaminated blood transfusions or unprotected sexual contact [3] and progresses to long-term HBV infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Aberra et al [ 19 ] reported that 90% of Ethiopian patients with CHB were HBeAg negative. Similarly, studies conducted in other sub-Saharan Africa countries found that the prevalence of HBeAg-negative chronic HBV infection ranged from 80%-93%[ 32 , 33 ]. Previous studies have reported a lower rate of HBeAg-positive chronic HBV infection in African patients with CHB than in those in the Far East, possibly attributed to geographical variability in HBV genotypes[ 21 , 22 , 34 ].…”
Section: Discussionmentioning
confidence: 97%
“…Aberra et al [ 19 ] reported that 90% of Ethiopian patients with CHB were HBeAg negative. Similarly, studies conducted in other sub-Saharan Africa countries found that the prevalence of HBeAg-negative chronic HBV infection ranged from 80%-93%[ 32 , 33 ]. Previous studies have reported a lower rate of HBeAg-positive chronic HBV infection in African patients with CHB than in those in the Far East, possibly attributed to geographical variability in HBV genotypes[ 21 , 22 , 34 ].…”
Section: Discussionmentioning
confidence: 97%
“…It is detected at the earliest stage of infection (one month after HBV exposure), rises to a peak level about 3 months later, and then steadily declines in chronic infection or vanishes at the time of HBV recovery [ 41 ]. HbsAg, the first virological marker to be found on the viral surface, indicates an acute HBV infection [ 42 , 43 , 44 ]. As HbsAg is a predominant viral marker, HBV serology can typically be detected as early as 1–2 weeks or as late as 11–12 weeks after the first infection.…”
Section: Diagnosis Of Hbvmentioning
confidence: 99%